THU0422 SEL-212: enhanced serum uric acid control in hyperuricemic patients through selective mitigation of anti-drug antibodies against pegsiticase. (15th June 2017) - Sands, E; Kivitz, A; Johnston, L; Kishimoto, TK
Abstract : Background: Recent EULAR recommendations for refractory gout treatment with pegylated uricase (pegloticase) acknowledge the risk of allergic reactions related to the development of anti-drug antibodies (ADAs) [1]. ADAs also affect the efficacy of treatment [2]. As a novel approach to treatment, we demonstrated that co-administration of pegsiticase (another pegylated uricase) and a synthetic vaccine particle encapsulating rapamycin (SVP-R) showed improved control of serum uric acid (sUA) in uricase-deficient mice by inducing antigen-specific immune tolerance to pegsiticase [3]. Here we describe the impact of SEL-212, a combination product of SVP-R and pegsiticase, on ADA formation and sUA levels in hyperuricemic patients in a Phase 1 open-label multicenter clinical trial. Objectives: To assess the initial safety and impact on sUA levels and ADA formation of SEL-212, which is designed to be the first non-immunogenic uricase therapy for refractory gout. Methods: Cohorts of hyperuricemic (sUA ≥6 mg/dL) patients consented to a single dose of 0.4 mg/kg pegsiticase alone, SVP-R alone (0.03–0.5-mg/kg), or 0.4 mg/kg pegsiticase co-administered with SVP-R (0.03–0.3-mg/kg; SEL-212). ADAs and sUA were assessed at baseline and 7, 14, 21, and 30 days after dosing. Results: Sixty-three patients were enrolled with a median age of 49.4 years. Mean baseline sUA was 7.4±1.3 mg/dL. Patients dosed with pegsiticase alone showed an immediate drop in sUA, which returned to baseline levels by 14–21 days in 4 of 5 subjects, correlating with the induction of ADA titers >1000. Patients treated with SVP-R alone showed no meaningful change in sUA. In contrast, patients treated with SEL-212 showed a dose-dependent inhibition of anti-uricase ADAs and corresponding decrease in sUA levels through at least day 30 after a single injection. Seven of 10 patients treated with SEL-212 at a SVP-R dose of 0.1 mg/kg showed no detectable sUA at day 30, and all 10 subjects dosed with SEL-212 at SVP-R doses of 0.15 or 0.3 mg/kg showed sustained control of sUA through at least day 30. There was a strong correlation between maintenance of low uric acid levels at day 30 and with low or no ADA titers. SEL-212 was generally well tolerated at effective dose levels. One SAE (grade 2 rash) was observed in the lowest of the three effective dose levels (0.1 mg/kg SVP-R). A second SAE was determined by the investigator to be not related to study drug. All SAEs fully resolved. No SAEs were observed with SEL-212 at the higher effective dose levels of SVP-R (0.15 or 0.3 mg/kg). The maximum tolerated dose was defined at 0.3 mg/kg. Conclusions: Data suggest that a single dose of SEL-212 in hyperuricemic patients can tolerably, therapeutically and durably control sUA for ≥30 days, correlating with inhibition of ADAs. These results supported monthly dosing in an ongoing Phase 2 multi-dose study in symptomatic gout patients and the potential use of SVP-R to mitigate ADAs for other immunogenic biologics. References: Richette P, et al., 2017, 76:29–42. Lipsky PE, et al., Arthritis Res Ther. 2014, 16:R60. Kishimoto, TK, et al., Nat Nanotechnol. 2016, 11:890–899. Disclosure of Interest: E. Sands Employee of: CMO for Selecta Biosciences, A. Kivitz: None declared, L. Johnston Employee of: COO for Selecta Biosciences, T. K. Kishimoto Employee of: CSO for Selecta Biosciences